Kemampuan Anak Dalam Bercerita Pengalaman Sederhana Di Depan Kelas - Renti Patricia; Nurul Haromaini Hanif; Siti Nabila; Tasya Ade Mutia; Putri Apriani; Riska Julianti Amanda (STKIP ROKANIA, 2026)
This study aims to analyze children’s ability to retell simple experiences in front of the classroom and the factors that influence its development. The research uses a literature review (library research) method by collecting and analyzing relevant scientific sources such as journals, articles, and books related to storytelling skills, learning methods, and instructional media in early childhood and elementary education. Data analysis was conducted using the Miles & Huberman model, including data reduction, data display, and conclusion drawing. The results of the analysis show that children’s storytelling ability is influenced by both internal and external factors. Internal factors include self-confidence, motivation, and language competence such as vocabulary mastery and sentence structure. External factors include family environment, school environment, learning methods, and the use of instructional media. Various studies indicate that appropriate teaching strategies such as role-playing, storytelling based on experience, and the use of visual media (pictures, story cards, and videos) can significantly improve children’s confidence, fluency, and ability to organize stories coherently. Furthermore, teachers play a crucial role as facilitators, motivators, and models in developing children’s storytelling skills. A supportive and enjoyable classroom environment also contributes to improving students’ willingness to speak in front of the class. Overall, storytelling ability develops optimally when supported by effective teaching strategies, teacher involvement, and a conducive learning environment.